2020
DOI: 10.1038/s41598-020-64685-y
|View full text |Cite
|
Sign up to set email alerts
|

Relevance of Caspase-1 and Nlrp3 Inflammasome on Inflammatory Bone Resorption in A Murine Model of Periodontitis

Abstract: This study investigates the role of NLRP3 inflammasome and its main effector Caspase-1 in inflammation and alveolar bone resorption associated with periodontitis. Heat-killed Aggregatibacter actinomycetemcomitans (Aa) was injected 3x/week (4 weeks) into gingival tissues of wild-type (WT), Nlrp3-KO and Caspase1-KO mice. Bone resorption was measured by µCT and osteoclast number was determined by tartrate-resistant acid phosphatase (TRAP) staining. Inflammation was assessed histologically (H/E staining and immuno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 54 publications
0
39
1
Order By: Relevance
“…In contrast, A. actinomycetemcomitans infection in THP-1 macrophages can trigger robust expression of AIM2 rather than NLRP3, suggesting that activation of the AIM2 inflammasome may dominantly contribute to the defense against A. actinomycetemcomitans ( 164 ). Similar evidence shows that although NLRP3 expression is increased in RAW 264 cells infected with A. actinomycetemcomitans , it may not be the most vital player in promoting inflammatory bone loss in this scenario: inhibition of ROS and cathepsin B rather than Nlrp3 knockdown can prevent increased IL-1β secretion, and the bone resorption activity of osteoclasts differentiated from Nlrp3 -deficient macrophages of mice with experimental periodontitis induced by A. actinomycetemcomitans is even increased ( 250 , 251 ). However, recent studies have shown that A. actinomycetemcomitans and its cytolethal distending toxin induce caspase-1 cleavage and persistent expression of IL-1β and IL-18 via an NRLP3-dependent pathway in U937 macrophages and THP-1 macrophages by increasing ROS and ATP levels, but not in human gingival epithelial cells ( 252 , 253 ).…”
Section: Inflammasomes In Inflammatory Osteolysis Of the Alveolar Bonmentioning
confidence: 68%
“…In contrast, A. actinomycetemcomitans infection in THP-1 macrophages can trigger robust expression of AIM2 rather than NLRP3, suggesting that activation of the AIM2 inflammasome may dominantly contribute to the defense against A. actinomycetemcomitans ( 164 ). Similar evidence shows that although NLRP3 expression is increased in RAW 264 cells infected with A. actinomycetemcomitans , it may not be the most vital player in promoting inflammatory bone loss in this scenario: inhibition of ROS and cathepsin B rather than Nlrp3 knockdown can prevent increased IL-1β secretion, and the bone resorption activity of osteoclasts differentiated from Nlrp3 -deficient macrophages of mice with experimental periodontitis induced by A. actinomycetemcomitans is even increased ( 250 , 251 ). However, recent studies have shown that A. actinomycetemcomitans and its cytolethal distending toxin induce caspase-1 cleavage and persistent expression of IL-1β and IL-18 via an NRLP3-dependent pathway in U937 macrophages and THP-1 macrophages by increasing ROS and ATP levels, but not in human gingival epithelial cells ( 252 , 253 ).…”
Section: Inflammasomes In Inflammatory Osteolysis Of the Alveolar Bonmentioning
confidence: 68%
“…A previous study revealed that intracellular LPS or inflammatory caspases were required for the activation of GSDMD ( Rathinam et al, 2019 ). As elevated levels of LPS from gram-negative bacterial and inflammatory caspases were often detected in patients with periodontitis and in murine periodontitis, this provided a prerequisite for the activation of GSDMD and IL-1β release ( Cheng et al, 2017 ; Rocha et al, 2020 ). In this work, we also confirmed that the activation of caspase-4/11 was elevated in human periodontitis samples and in murine periodontitis models and that P. gingivalis (a gram-negative periodontopathogen) induced PDLSC pyroptosis with the cleavage of GSDMD and IL-1β release.…”
Section: Discussionmentioning
confidence: 99%
“…: (i) NLRP3 regulates alveolar bone loss in ligature-induced periodontitis by promoting osteoclastic differentiation; (ii) MCC950 suppresses alveolar bone loss with reduced IL-1β activation and osteoclast differentiation in ligature-induced periodontitis.Several studies have reported the important role of NLRP3 in periodontitis, with the focus on the function of NLRP3 on macrophage12 or periodontal ligament cells 27. To the best of our knowledge, the first report focused on the effects of NLRP3 on osteoclast differentiation in periodontitis, found that NLRP3 inflammasome does not have a relevant role in the inflammatory bone resorption 28. These results are in contrast with those of a study that used a Porphyromonas gingivalis oral colonization model of experimental periodontitis, which showed a significant attenuation of bone resorption in NLRP3-deficient mice 12.…”
mentioning
confidence: 99%